Cape Verde : Country Procurement Assessment Report, Volume 1. Executive Summary - World Bank (Washington, DC, 2013)
Cape Verde is different in that it does not have a national code governing the procurement of goods/equipment or the performance of work, other than the use of consultants' services; it merely has arrangements set forth in decrees that govern procurement in specific sectors. In this regard, the only structured text that exists has been drafted for infrastructure (civil engineering work). This Country Procurement Assessment Report (CPAR) includes two volumes, the executive summary -- consisting of conclusions regarding the five pillars of the CPAR, and the analytical report -- which includes in-depth analysis of the five pillars.